2021
DOI: 10.1080/07391102.2021.1902858
|View full text |Cite
|
Sign up to set email alerts
|

COVID19-inhibitory activity of withanolides involves targeting of the host cell surface receptor ACE2: insights from computational and biochemical assays

Abstract: SARS-CoV-2 outbreak in China in December 2019 and its spread as worldwide pandemic has been a major global health crisis. Extremely high infection and mortality rate has severely affected all sectors of life and derailed the global economy. While drug and vaccine development have been prioritized and have made significant progression, use of phytochemicals and herbal constituents is deemed as a low-cost, safer and readily available alternative. We investigated therapeutic efficacy of eight withanolides (derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…Docking is a tool used to identify the best orientation of the molecules (protein-ligand) to bind, and form the stable complex. To rank the docked poses, and explore the binding affinity, prime MM-GBSA Schrödinger tool 2019–2 was used [ 33 ]. MM-GBSA is generally used to approximate the binding affinity of the ligands [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Docking is a tool used to identify the best orientation of the molecules (protein-ligand) to bind, and form the stable complex. To rank the docked poses, and explore the binding affinity, prime MM-GBSA Schrödinger tool 2019–2 was used [ 33 ]. MM-GBSA is generally used to approximate the binding affinity of the ligands [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…SARS-CoV-2 manifested complications that include the CNS, PNS, and neuromuscular system, range from mild to severe, and can also appear in patients with asymptomatic SARS-CoV-2 infection. SARS-CoV-2 infects the host by establishing the binding of its spike (S) glycoproteins to the host ACE2 receptor that expresses in the brain, gastrointestinal tract (GI), respiratory tract, lung parenchyma, and endothelial cells, and therefore it serves as a potential target for the direct COVID-19 inhibitory regimens (Kalra et al, 2021 ) or indirect suppressive strategies including miRNAs (Li et al, 2018 ). The most common symptoms associated with SARS-CoV-2 are dry cough, fever, and lethargy; however, aged adults are more susceptible to severe infection involving shortness of breath, pneumonia, and acute respiratory distress syndrome (ARDS) leading to higher mortality incidence ( Table 1 ).…”
Section: Sars-cov-2 Manifested Neurological Complicationsmentioning
confidence: 99%
“…In the case of TMPRSS2, the grid was generated by choosing the three main catalytic residues namely, His 296 , Asp 345 , and Ser 441 [40]. While for ACE2, it was found that in the native crystal structure, Ser 19 , Gln 24 , Lys 34 , Glu 35 , Asp 38 , and Gln 42 of ACE2 were involved in the hydrogen bonding with receptor binding domain of Spike protein [41]. So, the grid was generated around these interacting residues.…”
Section: Grid Generation and Molecular Dockingmentioning
confidence: 99%
“…The docking score of Mortaparib Plus was considerably higher at the binding site of M pro (−4.98 kcal/mol) in comparison to the host cell surface proteins-TMPRSS2 and ACE2. In the case of M pro -Mortaparib Plus best docking pose, His 164 was making hydrogen bonds while the other crucial catalytic residues-His 41 and Thr 190 of M pro were involved in other polar and hydrophobic interactions (Figure 5A). The docking score and details of interacting residues are listed in Table 2.…”
Section: Mortaparib and Mortaparib Plus As A Potential Inhibitor Of Viral Protein M Promentioning
confidence: 99%